Simultaneous surgical treatment of primary ovarian carcinoid and carcinoid heart disease - Uladzimir Andrushchuk; Aliaxandr Saevich; Viktoria Ermochenko; Mikalai Shchatsinka (Termedia Publishing House, 2022)
The incidence of neuroendocrine tumors (NET) is 2.5-5 per 100 000 population. Up to 20% of patients with NET develop carcinoid syndrome (CS), and in 40-50% of those carcinoid heart disease (CHD) is reported (0.27 per 100 000 population per year) [1]. Development of CS and CHD is determined by numerous vasoactive substances (serotonin, kallikrein, bradykinin, histamine, prostaglandins, etc.) which are produced by NET [2]. Primary ovarian carcinoid is a rare disease and accounts for 0.3-1.0% of all carcinoid tumors and up to 0.1% of ovarian tumors [3]. Venous drainage from ovaries, as from other paired organs, bypasses the liver and enters the vena cava inferior, which is the main reason for early development of CS and manifestation in ovarian carcinoids. Typical clinical symptoms of CS include flushing (90%), diarrhea (70%), wheezing (15%), fatigue, hypotension and arrhythmias [4]. Treatment of CS is a challenge due to often late diagnostics, life-threatening carcinoid crises and lack of established guidelines for surgical treatment of ovarian tumors, associated with CHD [5].